2007
DOI: 10.1128/jb.01080-06
|View full text |Cite
|
Sign up to set email alerts
|

The Thiol:Disulfide Oxidoreductase DsbB Mediates the Oxidizing Effects of the Toxic Metalloid Tellurite (TeO32−) on the Plasma Membrane Redox System of the Facultative PhototrophRhodobacter capsulatus

Abstract: The highly toxic oxyanion tellurite (TeO 3 2؊ ) is a well known pro-oxidant in mammalian and bacterial cells. This work examines the effects of tellurite on the redox state of the electron transport chain of the facultative phototroph Rhodobacter capsulatus, in relation to the role of the thiol:disulfide oxidoreductase DsbB. Under steady-state respiration, the addition of tellurite (2.5 mM) to membrane fragments generated an extrareduction of the cytochrome pool (c-and b-type hemes); further, in plasma membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 47 publications
3
24
0
Order By: Relevance
“…It has been observed for some time that in the environment, many Pseudomonas spp. accumulate inactivating mutations specifically in a twocomponent regulatory system comprised of the GacS and GacA proteins (van den Broek et al, 2005). Recently it was shown that gacSmutants of P. aeruginosa biofilms respond to metal and other stresses by producing hyper-biofilm forming, stress-resistant phenotypic variants (Davies et al, 2007), and we have observed a similar effect in P. fluorescens (our unpublished data).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It has been observed for some time that in the environment, many Pseudomonas spp. accumulate inactivating mutations specifically in a twocomponent regulatory system comprised of the GacS and GacA proteins (van den Broek et al, 2005). Recently it was shown that gacSmutants of P. aeruginosa biofilms respond to metal and other stresses by producing hyper-biofilm forming, stress-resistant phenotypic variants (Davies et al, 2007), and we have observed a similar effect in P. fluorescens (our unpublished data).…”
Section: Discussionsupporting
confidence: 72%
“…In terms of toxicity this has implications in numerous cellular processes involving redox reactions. As an example, recent work with membranes of Rhodobacter capsulatus and tellurite suggests that tellurite may be acting as an electron sink, pulling excess reducing power from the electron transport chain (Borsetti et al ., 2007). The importance of redox chemistry in toxicity is also exemplified by the ability of redox‐active metals, such as Fe, Cu, Ni, Cr, V and Zn, to cause oxidative stress (Stohs and Bagchi, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Tellurite is known to activate the machinery of resistance to oxidative stress in E. coli and Pseudomonas pseudoalcaligenes that includes NADPH/glutathione-mediated reactions [2,4,13,15]. In Rhodobacter capsulatus, a thiol:disulfide oxidoreductase was shown to participate in electron transport resulting in the reduction of tellurite [16]. Several tellurium-resistant genes have been identified in E. coli (ter, kilA and tehAB operons) [5] and other bacteria such as R. sphaeroides ( One aspect not defined for all bacterial systems regarding the tellurite metabolism is its transport system.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the proposed mechanisms of Te-oxyanions bioconversion in microorganisms are similar to those described for Se-species [13,56,88,104,108]. Further, TeO 3 2− processing in microorganisms have been ascribed to enzymatic reductions by periplasmic or cytoplasmic oxidoreductases [107,109], such as nitrate reductases [109,110], catalases [111] and thiol:disulfide oxidoreductase [112]. However, the function of all these enzymes for bioconverting Te-oxyanions appears to be not specific, leading to a low resistance level toward Te-species in these microorganisms.…”
Section: mentioning
confidence: 83%